The cultural competence of health professionals in the care of cancer patients: a scoping review - Jeisson Andrés Hincapié-Carvajal; Zelibeth Cedeño-Camaño; Nataly Igualá-González; Alba Luz Martínez-Salazar; Arian Martínez-Sandoya; Saidy Eliana Arias-Murcia (Revista Gaúcha de Enfermagem)
ABSTRACT Objective: To explore the available evidence on the cultural competence of health professionals in the care of cancer patients. Methods: Scoping review carried out between April and May 2024. The databases Scopus, Medline (via Pubmed) and BVS (Lilacs) were used as sources. The sample included articles from the last ten years, resulting from primary research, literature reviews and systematic reviews in English, Portuguese and Spanish. Data were manually extracted and analyzed using an inductive thematic construction process. Results: 31 studies were included, mostly quantitative research produced in North America. Four themes emerged from the synthesis: 1) Barriers to culturally competent care in oncology settings; 2) Strategies for implementing cultural practices; 3) Intervention measures to improve the cultural competence of oncology care providers; and 4) Outcomes of cultural competence on patient satisfaction and professional development. Conclusion: Evidence reveals that cultural barriers limit effective cancer care. However, strategies and interventions to improve cultural competence increase patient satisfaction and benefit providers' professional development in oncology care.